2014
DOI: 10.1371/journal.pone.0100788
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Season-Dependency in Vegetation Effects on Macrofauna in Temperate Seagrass Meadows (Baltic Sea)

Abstract: Seagrasses and associated macrophytes are important components of coastal systems as ecosystem engineers, habitat formers, and providers of food and shelter for other organisms. The positive impacts of seagrass vegetation on zoobenthic abundance and diversity (as compared to bare sands) are well documented, but only in surveys performed in summer, which is the season of maximum canopy development. Here we present the results of the first study of the relationship between the seasonal variability of seagrass ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…While we summarize these published studies in terms of habitat-specific seasonality, another logical framing is that habitat structure matters more for nekton assemblages during seasonally high biomass of seagrass-that is, season-specific habitat effects. Seasonality in the degree of habitat provision by seagrass has also been reported for infaunal assemblages (Włodarska-Kowalczuk et al 2014).…”
Section: Introductionmentioning
confidence: 77%
“…While we summarize these published studies in terms of habitat-specific seasonality, another logical framing is that habitat structure matters more for nekton assemblages during seasonally high biomass of seagrass-that is, season-specific habitat effects. Seasonality in the degree of habitat provision by seagrass has also been reported for infaunal assemblages (Włodarska-Kowalczuk et al 2014).…”
Section: Introductionmentioning
confidence: 77%
“…Comparable data on the taxa comprising each benthic macrofaunal assemblage and on their relative importance were obtained from the datasets underlying recent published work in intertidal Zosterella habitats carried out at equivalent times of the year (Wlodarska‐Kowalczuk et al ., ) and with the same methodology: (1) on Scolt Head Island (within the Scolt Head National Nature Reserve) in the northwestern European North Sea at 53°N01°E (Barnes & Ellwood, ; Barnes, ), (2) at Knysna (within the Garden Route National Park) on the Indian Ocean coast of South Africa at 34°S23°E (Barnes & Ellwood, , ; Barnes, ; Barnes & Barnes, ) and (3) on North Stradbroke Island (within a Habitat Protection Zone of the Moreton Bay Marine Park) Queensland at 27°S153°E (Barnes & Barnes, ; Barnes & Hamylton, ; Barnes, ). All sites are hence enclosed within areas of high conservation status.…”
Section: Methodsmentioning
confidence: 99%
“…were recorded in the present study as well and found restricted to the mangrove zone. It was known that these species are instantly climb down from the tree trunks or prop roots to the mangrove floor for feeding when the ebb tide starts and again climb up during the high tide [24].…”
Section: Variabilities Of Mollusc Assemblagesmentioning
confidence: 99%